Adenovirus based HPV L2 vaccine induces broad cross-reactive humoral immune responses. Issue 30 (16th July 2018) - Vujadinovic, Marija; Khan, Selina; Oosterhuis, Koen; Uil, Taco G.; Wunderlich, Kerstin; Damman, Sarra; Boedhoe, Satish; Verwilligen, Annemiek; Knibbe, Jonathan; Serroyen, Jan; Schuitemaker, Hanneke; Zahn, Roland; et al.
Abstract: Oncogenic high-risk human papillomavirus (HPV) infections cause a substantial number of genital and non-genital cancers worldwide. Approximately 70% of all cervical cancers are caused by the high-risk HPV16 and 18 types. The remaining 30% can be attributed to twelve other high-risk HPV-types. Highly efficacious 2-valent, 4-valent and 9-valent L1 protein based prophylactic HPV vaccines are available however with limited cross-protection. To further increase the coverage, development of a multivalent cross-protective HPV vaccine is currently focused on the conserved N-terminus of HPV's L2 protein. We have developed a vaccine candidate based on the rare human adenovirus type 35 (HAdV35) vector that displays a concatemer of L2 protein epitopes from four different HPV-types via protein IX (pIX). A mix of two heterologous HAdV35 pIX-L2 display vectors present highly conserved linear epitopes of nine HPV-types. Each HAdV35 pIX-L2 display vector exhibits a good manufacturability profile. HAdV35 pIX-L2 display vaccine vectors were immunogenic and induced neutralizing antibodies against HPV-types included in the vaccine and cross-neutralizing antibodies against distant a HPV-type not included in the vaccine in mice. The HAdV35 pIX-L2 display vectors offer an opportunity for a multivalent HAdV-based prophylactic HPV vaccine.